La mobilité, clé de nouvelles pratiques ? - Laurent Jeannin
Many announcements are made for several years on the need to articulate the structure of school spaces and equipments in order to encourage learners Development (Mazalto 2005 Oblinger 2006, Lippman, 2010, eve folder of IFE 2012 "Clever Classroom" 2015, the UK Higher Education Learning Space Toolkit 2016 emergence of Learning'Lab, Fab'Lab ...) The awards are given to school furniture (Price Jean Prouvé 2015) and to institutions, price the innovative establishment (September 2016) in college JP Rameau under his ECLA project : school of the Future 'an area of « educational innovation in the digital area ». Is this an announcement effect, or a mutation of the spaces is running? Is this a display effect from donors or industrial partners? If this transition is announced, how it fits you or how does it demand a drift standards? and finally what financial envelope we talking about?